Preposition Stranding in Spanish–English Code-Switching - Bryan Koronkiewicz (Languages, 2022)
This study tests the acceptability of preposition stranding in the intrasentential code-switching of US heritage speakers of Spanish. Because languages vary when extracting determiner phrases from prepositional phrases, known as preposition stranding or p-stranding, a contrast arises for Spanish–English bilinguals. English allows p-stranding, but in Spanish the preposition is traditionally pied-piped with the DP. Heritage speakers of Spanish, though, have shown variability, with child sequential bilinguals requiring said pied-piping, but simultaneous bilinguals allowing p-stranding in Spanish. Participants (n = 24) completed a written acceptability judgment task with a 7-point Likert scale. The task included code-switched sentences (n = 16) with p-stranding, switching from either English to Spanish or vice versa, with comparison monolingual equivalents for Spanish (n = 8) and English (n = 8) included as well. The results found that the simultaneous bilinguals accepted p-stranding in both languages, while also showing no restriction in either code-switching condition. Child sequential bilinguals, however, showed the expected monolingual distinction between Spanish and English, and p-stranding was only accepted with Spanish determiner phrases extracted from an English prepositional phrase (i.e., Spanish-to-English). These findings support the previously reported differentiation between simultaneous and child sequential bilinguals regarding p-stranding, while expanding it to code-switching.